Impacts of Firm Characteristics on Mining Companies Capital Structure - Grace Marvellous Ryanata; Tita Deitiana (Pusat Penelitian dan Pengabdian kepada Masyarakat Sekolah Tinggi Ilmu Ekonomi Trisakti, 2022)
This research is made with the main purpose of analyzing the impacts of firm-level determinants of capital structure that include profitability, firm size, liquidity, non-debt tax shield, as well as asset tangibility. The objects of this research are mining companies listed on the Indonesian Stock Exchange for the period 2012-2020. The sample of this research comprises of 7 companies that have been selected through the use of purposive sampling method and uses multiple regression with panel data approach as the method of data analysis. The result of this research shows that all variables except for firm size have an impact on capital structure. Profitability, liquidity, non-debt tax shield, asset tangibility are found to negatively impact capital structure.